An economic history of the Champagne contracts, lessons for regional development - Jean-Baptiste Traversac; Hervé Lanotte (European Regional Science Association (ERSA), 2011)
This paper highlights the success factors of the governance of the Champagne supply chain. Scholars on economic organisation stress the role of the contractual enforcement to explain the stability of the economic exchanges and the ability of the economic and political actors to foster their own development (NORTH 1999). Our contribution detailed explicit and implicit mechanisms related to the vinegrower-merchant relations in the regional system. The Champagne region had the particularity to posses a double-head organisation, regrouping all the farms and firms involved in the agronomic, and commercial process of the regional wines. This private board is supported by an institutional environment, common market organisation, French rural acts, and national and international legislations on geographical indication. These legislatives and administrative components define precisely the productive and market rules. Rely on a longitudinal approach we reinterpret the way the interprofessionnal (general) agreement, essential part of the governance of the regional market, evolved during decades (BARRERE 2003). This rereading illustrates the interdependency between explicit and implicit enforcement mechanisms which foster the cooperation. We argue that asymmetric investments in advertising play a major role in the stability of the regional cooperation. The achievement of the reputation of the AOC Champagne by massive advertising and commercial investments mainly realised by the negociants is central to understand the convergence of both party strategies on a long term. These investments step in as catalyst of a negotiated environment and award the self-enforcing character of the contracts. It makes efficient the set of private arrangements and regulatory mechanisms designed to eradicate opportunistic behaviours. During all the second part of the 20th century, the form of the contractual agreements evolved. Governance tools were added and suppressed. However these forced or desired adaptations slightly alter the nature of the cooperative process. The flexibility of the private arrangement, as well as the comprehensive economic policy, ensures the durability of the general agreement in spite of crisis. These results backup the hypothesis of the new institutional economics on the necessity of complementary institutions to make the market efficient (AOKI 2001).
Keywords: 330